TMT-Based Proteomic Explores the Influence of DHEA on the Osteogenic Differentiation of hBMSCs - Liang, Xiaonan; He, Mingwei; Zhu, Bo; Zhu, Yongjia; He, Xixi; Liu, Dachang; Wei, Qingjun (Frontiers in Cell and Developmental Biology, 2021)
Dehydroepiandrosterone (DHEA) has been revealed to implicate in facilitating osteoblast differentiation of human bone marrow mesenchymal stem cells (hBMSCs) and inhibiting osteoporosis (OP). However, the underlying molecular mechanism remains largely unknown. Here, we induced osteogenic differentiation of hBMSCs derived from elders using an osteogenic induction medium with or without DHEA. The results showed that osteogenic induction medium (OIM) with DHEA could significantly promote the proliferation and osteogenic differentiation of hBMSCs than OIM alone. By using a Tandem Mass Tag (TMT) labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) technology, we screened out 604 differentially expressed proteins (DEPs) with at least one unique peptide were identified (524: OIM vs complete medium (CM), and 547: OIM+DHEA vs CM), among these proteins, 467 DEPs were shared in these two different comparative groups. Bioinformatic analysis revealed these DEPs are mainly enriched in metabolic pathways. Interestingly, the expression levels of the DEPs in the metabolic pathways showed a more noticeable change in the OIM+DHEA vs CM group than OIM vs CM group. Moreover, the protein-protein interaction (PPI) network analysis revealed that three potential proteins, ATP5B, MT-CYB, and MT-ATP6, involved in energy metabolism, might play a key role in osteogenic differentiation induced by OIM+DHEA. These findings offer a valuable clue for us to better understand the underlying mechanisms involved in osteoblast differentiation of hBMSCs caused by DHEA and assist in applying DHEA in hBMSCs-based therapy for osteogenic regeneration.